Spinning the escape, unraveling the silence: images as devices of resistance and creation (Revista de Ensino em Artes, Moda e Design, 2025)
This article aims to understand how images operate as devices for creating tactics of subversion, forging other ways of narrating and inspiring teaching in cyberculture. If educating is about composing meanings, it is also a creative act, an action that humanizes, requiring a sensitive listening that is open to otherness. Therefore, as educators, we reaffirm the need for a teaching practice that recognizes the power of emotions and experiences, allowing for the invention of other ways of being/in the world. In light of this, we explore the movements of cyberculture and its circulating images. Our theoretical-epistemological choice was for Research with Everyday Life and the method of online cartography. We mapped images and some comments on the social network Instagram from the user @mayaraferrao. As a finding of the research, we observed that these movements not only expand the aesthetic dimensions of images but also unfold them into others, serving as devices of resistance and creation that forge new ways of narrating and inspiring teaching in contemporary times.
Keywords: Education; Images; Ciberculture; Creation; Movements